Visualization of Fast Food Restaurant Location using Geographical Information System. (April 2018) - Widaningrum, D L; Surjandari, I; Arymurthy, A M
Abstract: The fast food restaurant industry, as one of the food service formats, has been growing significantly in Indonesia, and still continuing in the future. Understanding of consumer behavior, as well as its various influence factors, such as demographic and socioeconomic factors, are needed to be done to support decisions in a business perspective. The purpose of this research is to study the utilization of various data visualized with Geographical Information System approach, to support the decision-making process, especially related to location analysis. Fast food restaurants in Jakarta were selected as the object of this research. The results show the various information generated from the developed geographic information system and some future research were also addressed in this article.